Painel de indicadores bibliométricos e de sustentabilidade para monitoramento científico e tecnológico sobre plantas endêmicas da Amazônia brasileira - Cristina-Silva, Luana (Universidade Federal de São Carlos, 2026)
This research stems from the importance of natural bio-inputs from the Brazilian Amazon biome and the risks associated with extractivism and other degradation factors affecting these resources. Research concerning "endemic plants of the Brazilian Amazon phytogeographic domain" spans multiple fields of knowledge, featuring diverse objectives and perspectives. Within this context, however, a gap is observed regarding bibliometric indicators capable of mapping and monitoring the scientific and technological production on this subject for analytical, diagnostic, or predictive purposes. Accordingly, we hypothesize that a periodic monitoring system, comprising bibliometric and sustainability indicators, can facilitate the visualization of the dynamics of scientific and technological developments regarding endemic Amazonian plants. These indicators, intersecting with sustainability-aligned indicators, highlight both an opportunity and a research demand from the perspective of Information Science. The research is quantitative in nature and employed methods and techniques derived from bibliometrics. The search for scientific articles was conducted using the international multidisciplinary database Scopus, and the search for patents was conducted via Espacenet. Based on five main search queries (referring to 5 different taxonomic groups, totaling 1975 endemic species from the Brazilian Amazon), the analyzed dataset comprised 800 scientific articles and 153 patents. Additionally, a script pipeline for the automated data modeling process was created to optimize future stages of periodic indicator updates. A visualization dashboard with dynamic features was created using Google's Looker Studio. Partial results indicate that the proposed dashboard not only helps address the gap in indicator concentration but also offers several implications, given its simplified and intuitive design aimed at reducing the user's cognitive effort. Finally, this research corroborates the importance of monitoring contemporary scientific and technological activities related to the Amazon's exclusive natural resources, particularly from a sustainability perspective. Consequently, it highlights the relevance of this study and its contribution to Information Science and civil society as a whole.
Panel of bibliometric and sustainability indicators for scientific and technological monitoring of endemic plants of the Brazilian Amazon
Keywords: Amazônia; Bibliometria; Informação Ambiental; Painel; Sustentabilidade; Amazon; Bibliometrics; Environmental Information; Dashboard; Sustainability; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 10. Redução das Desigualdades; 3. Saúde e Bem-Estar